The Impact of Nanoparticles on Plant Growth, Development, and Stress Tolerance Through Regulating Phytohormones - Karabulut, Fadime (Springer Nature, 2024)
To enhance the production, nutritional value of plant-based products, and plant physiology, nanoparticles (NPs) are frequently used in agriculture. However, it is still unclear how nanoparticles are absorbed and transported. It is demonstrated in agriculture that plants can absorb nanoparticles and affect their physiological processes. Significant limitations that have a negative impact on the metabolic and developmental processes of plants are biotic stress factors. However, these results have not always been encouraging partially because NPs have occasionally been found to hurt plants by the potential of toxicity. Depending on the number of NPs applied, the stage of plant growth, and environmental factors, the relief of stress brought on by such NPs varies greatly. The activation of the antioxidant defense system, hormonal regulation, and stress are just a few examples of the physiological and biochemical processes that NPs are thought to be regulatory molecules for plants that can modulate. Plant growth hormones are known to participate in a variety of signaling cascades and function as molecules that regulate stress when exposed to nanoparticles. Reactive oxygen species (ROS), which can be controlled with the help of nanoparticles, are produced more frequently when under stress. According to recent research, nanoparticles can strengthen the effects of stress by regulating phytohormone signaling. This section discusses the phytotoxicity of NPs, how it affects plant growth and cell structure, and the underlying mechanisms that lead to damage and the oxidative stress response. In addition, this study will be beneficial for ensuring the longevity of nanoparticles used in agricultural production and directing their rational application. © The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2024.
Keywords: Biotic stress; Nanoparticles; Phytohormone; Plant physiology